2022
DOI: 10.3390/ijerph19159586
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Modeling of COVID-19 to Classify the Infection and Death Rates in a Specific Duration: The Case of Algerian Provinces

Abstract: COVID-19 causes acute respiratory illness in humans. The direct consequence of the spread of the virus is the need to find appropriate and effective solutions to reduce its spread. Similar to other countries, the pandemic has spread in Algeria, with noticeable variation in mortality and infection rates between regions. We aimed to estimate the proportion of people who died or became infected with SARS-CoV-2 in each provinces using a Bayesian approach. The estimation parameters were determined using a binomial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…A study of spatiotemporal diffusion of COVID-19 in Algeria found that the virus was suspected to have increased transmission in the northern parts of the country [8]. In a separate study, aimed to classify the risk of deaths and the spread of infections across various provinces in the country, several regions and areas were identified that required more attention and resources to control the spread of the virus [9]. Furthermore, another study highlighted the idea that the impact of the virus is not uniform across all cultural and ethnic groups [10].…”
Section: Impacts Of Covid-19 In Algeriamentioning
confidence: 99%
“…A study of spatiotemporal diffusion of COVID-19 in Algeria found that the virus was suspected to have increased transmission in the northern parts of the country [8]. In a separate study, aimed to classify the risk of deaths and the spread of infections across various provinces in the country, several regions and areas were identified that required more attention and resources to control the spread of the virus [9]. Furthermore, another study highlighted the idea that the impact of the virus is not uniform across all cultural and ethnic groups [10].…”
Section: Impacts Of Covid-19 In Algeriamentioning
confidence: 99%
“…Recognizing the high cost and insufficient resources due to the strict quarantine policies, many countries are working to develop models for predicting future outbreaks so as to rationally utilize medical resources ( 46 ). There are also researchers who monitor transmission and death through models to improve their predictive ability ( 47 ). Whether these monitoring and preventive measures are properly used has an important impact on the prevention and control results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As of December 2022, approximately 579 million people have been infected, leading to 6.6 million fatalities [4]. Some forecasts of the number of COVID-19 cases using Bayesian regressions may help governments to take actions to avoid the disease's spread [5][6][7]. Vaccines against SARS-CoV-2 were developed rapidly and are now in wide use.…”
Section: Introductionmentioning
confidence: 99%